2013
DOI: 10.4155/fmc.12.202
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Targeting Lipid Aldehydes and Lipoxidation End-Products in the Treatment of Ocular Disease

Abstract: Lipoxidation reactions and the subsequent accumulation of advanced lipoxidation end products (ALEs) have been implicated in the pathogenesis of many of the leading causes of visual impairment. Here, we begin by outlining some of the major lipid aldehydes produced through lipoxidation reactions, the ALEs formed upon their reaction with proteins, and the endogenous aldehyde metabolizing enzymes involved in protecting cells against lipoxidation mediated damage. Discussions are subsequently focused on the clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 190 publications
1
21
0
Order By: Relevance
“…However, this is unlikely to occur exclusively through elevated oxidative stress and lipoxidation since other lipid aldehydes and ALEs fail to accumulate in Müller cells during diabetes. 10,22 Therefore, we were interested in exploring whether the accumulation of FDP-lysine adducts in retinal Müller glia might be associated with the downregulation of specific ACR detoxifying ALDH and AKR enzymes in these cells. Of the ALDH and AKR genes found to be expressed in the retina (Fig.…”
Section: Diabetes Downregulates Müller Glia Aldh1a1 Protein Expressionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this is unlikely to occur exclusively through elevated oxidative stress and lipoxidation since other lipid aldehydes and ALEs fail to accumulate in Müller cells during diabetes. 10,22 Therefore, we were interested in exploring whether the accumulation of FDP-lysine adducts in retinal Müller glia might be associated with the downregulation of specific ACR detoxifying ALDH and AKR enzymes in these cells. Of the ALDH and AKR genes found to be expressed in the retina (Fig.…”
Section: Diabetes Downregulates Müller Glia Aldh1a1 Protein Expressionmentioning
confidence: 99%
“…8 Although ROS may directly affect cell function, in recent years increasing evidence has suggested that many of the detrimental effects of oxidative stress result from ROS-induced lipid peroxidation reactions. [9][10][11] Lipid peroxidation causes the formation of a number of lipid aldehyde byproducts, including malondialdehyde (MDA), 4-hydroxynonenal (4-HNE), and acrolein (ACR). These aldehydes are toxic, at least in part, due to their ability to react with cellular and tissue proteins leading to the formation of advanced lipoxidation end products (ALEs) which induce protein dysfunction and alter cellular responses.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of the reported ALDH2-induced protection against aldehyde-related diseases, we speculated that ALDH2 might also be able to alleviate retinal diseases [18]. Alda-1 (N-[1,3-benzodioxol-5-ylmethyl]-2,6-dichlorobenzamide) is a ALDH2 activator, which specifically increases the expression of ALDH2 and its enzymatic activity [6].…”
Section: Introductionmentioning
confidence: 99%